Reduction of Lumbar Spondylolisthesis, Surgical Technique and Clinical Outcome. - Mohamed Eshra (Egyptian Spine Association, 2013)
Background Data: Reduction of the slipped vertebrae as a part of surgical approach is now attempted. In the current literature, the studies have paid attention to the surgical reduction of the slippage or in situ spinal fixation technique. These studies have a lack of comparison between these variable techniques. Purpose: To define the role and benefits of reduction and stabilization of lumbar spondylolisthesis. Study Design: A retrospective clinical case study. Patients and Methods: 24 patients with low grade isthmic lumbar spondylolisthesis between January 2008 and June 2010 were enrolled for this study. Patients were treated by slip reduction, interbody fusion with or without cage and internal pedicle screw fixation. All patients had back pain and radicular pain for at least one year pre-operatively. All patients were examined by plain radiographs, CT scan and MRI. Oswestry Disability Index (ODI) was used for pre and post-operative clinical assessment in all cases. Radiological assessment for bony fusion was done using plain radiography and CT scan. All patients were followed up both clinically and radiologically for at least one and half years. Results: The overall rate of neurological improvement after our procedures was 91%. Radicular pain improved earlier than back pain. Slip was reduced and satisfactory screw purchase was proved in all patients. Reported fusion rate was 92%. Operative and postoperative complications occurred in five patients but were minor and cured. Conclusion: Reduction of lumbar spondylolisthesis improved the clinical manifestations, increased the fusion rate and speed the return to normal or near normal life activities. (2013ESJ044)